2013
DOI: 10.1158/1541-7786.mcr-12-0468
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of the Tetraspanin CD151 Reduces Spontaneous Metastatic Spread of Prostate Cancer in the TRAMP Model

Abstract: Tetraspanins are integral membrane proteins that associate with motility-related molecules such as integrins. Experimental studies have indicated that they may be important regulators of tumor invasion and metastasis, and high expression of the tetraspanin CD151 has been linked to poor prognosis in a number of cancers. Here, we show for the first time that genetic ablation of CD151 inhibits spontaneous metastasis in a transgenic mouse model of de novo tumorigenesis. To evaluate the effects of CD151 on de novo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 46 publications
2
49
2
Order By: Relevance
“…Indeed, some tetraspanin members have been shown to play a role in cancer progression. A definite role for CD151 was demonstrated in two independently derived CD151KO mice that were challenged with several tumor models (16,19). In the same studies, diminished metastasis in CD151KO hosts was suggested to be due to impaired adhesion and trans-endothelial migration of CD151 expressing tumor cells (19).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, some tetraspanin members have been shown to play a role in cancer progression. A definite role for CD151 was demonstrated in two independently derived CD151KO mice that were challenged with several tumor models (16,19). In the same studies, diminished metastasis in CD151KO hosts was suggested to be due to impaired adhesion and trans-endothelial migration of CD151 expressing tumor cells (19).…”
Section: Discussionmentioning
confidence: 91%
“…Overexpression of these tetraspanins correlates with tumor progression and metastasis (15). Corroborating the role of CD151 in tumor progression are studies in CD151-deficient mice, which develop fewer metastases than their wild-type (WT) counterparts in carcinogen-induced skin cancer, melanoma (B16F10), Lewis lung carcinoma (LLC), transgenic breast cancer (MMTV-PyVmT), and adenocarcinoma prostate cancer (TRAMP) models (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The best characterized of the tetraspanin molecular partners are integrins. Indeed, in nonimmune cells the evidence that tetraspanins can regulate integrin-mediated functions is overwhelming, incorporating roles in wound healing (43), angiogenesis (44), hemostasis (45), epidermal integrity (46), glomerular filtration (47,48), and cancer cell metastasis (49)(50)(51). By comparison, the evidence that tetraspanins regulate adhesion and migration of leukocytes is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several tetraspanins gained special attention because they regulate the progression of various types of cancers or the formation of metastasis, perhaps as a consequence of their ability to regulate the migration of cancer cells and their ability to invade the surrounding matrix Hemler, 2014;Zöller, 2009). In particular, several experimental models, including genetic models of cancers (Copeland et al, 2013a;Copeland et al, 2013b;Deng et al, 2012), as well as clinical data, suggest that CD9 and CD82 are suppressors of metastasis, whereas CD151 and TSPAN8 promote metastasis (Hemler, 2014;Romanska and Berditchevski, 2011;Zöller, 2009).…”
Section: Introductionmentioning
confidence: 99%